A Study on Growing Trends, Customer Expectations and Perception towards Services Provided by OYO - Chua, Jia Feng; Kee, Daisy Mui Hung; Lee, Men Je; Lim, Chun Han; Toh, Yong Rong; Raj, Nidhi; Goel, Pragya; Pandey, Rudresh (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
This study has been carried out to identify the factors of growing trends, customer expectations, and perception of services provided by OYO hotels. The study has been done with the information published by the company official website as well as the customer's experiences and thought through answering a questionnaire. The findings and results of this study suggested that the most common factors which concern the online hotel booking users are amenities. Besides, the customer expectation towards OYO services has been categorized into information, procedure, and incidental services where information has the highest satisfactory. Lastly, perception towards initiative taken by OYO such as customer privacy control system, In-App SOS button, OYO Assists, and preventive measure during the outbreak of Covid-19 has been determined and evaluated.